Inclusive Society as a Necessary Condition for Knowledge-Based Competitiveness in the European Union - Anita Pelle; Renáta Laczi (Managing Global Transitions, 2015)
The latest growth strategy of the European Union, the Europe 2020, represents a new approach towards economic growth. From our point of view the most important innovation of the strategy is that, beside intelligent and sustainable growth, it sets out the establishment of an inclusive society as one of its priorities. We believe that member states’ competitiveness is a key factor of their economic growth. For that reason, we included the World Economic Forum’s Global Competitiveness Index in our analysis to find the relationship between competitiveness and an inclusive society. We investigate the eu member states’ performance on country group level, and then we set up an inclusive indicator based on the main components of the inclusive pillar of the Europe 2020 strategy. Our findings suggest that an inclusive society is one of the necessary conditions for economic prosperity.